A Cluster Dynamics Model for Accumulation of Helium in Tungsten under Helium Ions and Neutron Irradiation (Communications in Computational Physics, 2012)
A cluster dynamics model based on rate theory has been developed to describe the accumulation and diffusion processes of helium in tungsten under heliumimplantation alone or synergistic irradiation with neutron, by involving different typesof objects, adopting up-to-date parameters and complex reaction processes as well asconsidering the diffusion process along with depth. The calculated results under different conditions are in good agreement with experiments much well. The model describes the behavior of helium in tungsten within 2D space of defect type/size anddepth on different ions incident conditions (energies and fluences) and material conditions (system temperature and existent sinks), by including the synergistic effect ofhelium-neutron irradiations and the influence of inherent sinks (dislocation lines andgrain boundaries). The model, coded as IRadMat, would be universally applicable tothe evolution of defects for ions/neutron irradiated on plasma-facing materials.